Different flying method in producing 3d modeling reconstruction for single tree using aerial photograph of unmanned aerial vehicle / Suzanah Abdullah ... [et al.] - Abdullah, Suzanah; Tahar, Khairul Nizam; Abdul Rashid, Mohd Fadzil; Osoman, Muhammad Ariffin; Mohd Noor, Mohd Zulfadhli (2018)
This paper shows the product of 3D model of single tree using different views of digital images. Typically, the users of 3D modelling become vital in certain applications that require measurement to determine the height, width, lenght, volume ofthe object. There are several technologiesused to produce 3D models but requirehigh cost. However, currently, with an advanced in technology development, an Unmanned Aerial Vehicle (UAV) is one of the emergence technologiesthat offers solution to overcome the issues with a higher quality of result. UAV is widely used for aerial photograph and commonly used for collecting data in both small and larger areasor larger and small scales. More importantly,this technology is also effecient in producing three-dimensional (3D) information with a higher resolution image. Thus, the current paper attempts to demonstrate the ability of the UAV technology for 3D extraction of single tree using different flying method. This research adapts aquantitative method that implement the experimental process in data acquisition of single tree. Convergent and stereo configuration are employed duringphotography fordata acquisition.This paper presents results of 3D modelling reconstruction of single tree taken by UAV DJI 4 Pro.